Investigating a Structural Model of the Relationship Between the Usage of Communication Technologies and Violence Among Female Students in Bushehr Province - Amene Abbasi (فصلنامه زن و جامعه)
Introduction: As contemporary societies become increasingly complex, communication media have also become more intricate, exerting various effects on social issues, including social deviations. Violence, as one of the forms of social deviance, is a social issue that requires comprehensive assessment due to its wide-ranging implications. Therefore, this article examines the influence of communication technologies on violence among female students in Bushehr Province. Materials and Methods: A survey method was employed, utilizing a questionnaire tool to study the violent behaviors of 1,049 female students in Bushehr Province. The sampling method adopted was a multistage cluster sampling technique.Findings: The findings of this research indicate that communication technology variables are related to the disruption of family relationships and religious beliefs, as well as violent behaviors. Path analysis results reveal that the dependent variable of violent behaviors is directly affected by the communication technology variable (β = 0.46), accounting for 10% of the variance in the dependent variable. Accordingly, in the path model, only the communication technology variable has a direct significant impact on the dependent variable, while the effects of disrupted family relationships and religious beliefs are indirect. Furthermore, based on fit indices, the model demonstrates good fit with RMSEA (Root Mean Square Error of Approximation) of 0.042 and X2/DF (Chi-square divided by degrees of freedom) of 2.88.